A Bibliometric Study on the Development of Radio Broadcasting Literature - Anwar, Rully Khairul; Abidin, Asep Zainal; Winoto, Yunus (Jurnal Kajian Jurnalisme, 2025)
Radio broadcasting is a significant communication medium in modern society. Since the early 1900s, radio broadcasting has progressed alongside technological advancements and scholarly discussions. Thus, a bibliometric analysis of radio broadcasting is essential. This study utilized a bibliometric framework to identify trends, patterns, and advancements in radio broadcasting literature. The Scopus database was utilized for data collection via a bibliometric literature review. The gathered data was assessed through bibliometric indicators such as author review, journal analysis, country evaluation, and trend analysis. The research methodology is quantitative, focusing on numerical data and statistical analysis for data processing. Selecting the quantitative methodology was driven by the need to integrate the numerical data with statistical computations. Consequently, this study adopted a quantitative research framework employing bibliometric techniques. The findings revealed that most authors published few articles, while some had high citation counts, reflecting low productivity in this field. The journal "Journal of Radio and Audio Media" is acknowledged for its quality. The United States is the leading country in scholarly publications on radio broadcasting. Recent trends in the field include "radio broadcasting," "radio," "television broadcasting," and "digital radio." Enhancing author productivity and fostering cross-institutional collaboration in radio broadcasting research is crucial for further advancement.